(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article analyzes the importance of innovative technologies to improve the theoretical and practical grammatical competence of future English language teachers. Teaching based on the experiences of the world’s leading countries in teaching foreign languages, improving the quality of foreign language teaching using advanced and effective methods, innovative methods and training of advanced specialists - has become the main basis of the main content of the educational program.